THE STUDENTS’ ABILITY IN TRANSLATING DESCRIPTIVE TEXT: A Study at the English Department Students of FKIP Unilak - Dahler Dahler (ELT-Lectura, 2014)
This research was conducted to find out to what extent is the students’ ability in translatingdescriptive text at fifth semester of English Education Department of FKIP Lancang Kuning University. Theresearch using cross sectional survey design as evaluation program. The amount of the participant in thisresearch was 24 students selected by using convenience sampling technique. In order to collect the data of this research, the researcher used descriptive text as the instrument of test. In analyzing the data to categorize the students’ ability in translating descriptive text, the researcher used descriptive statistics. The students’ ability in translating descriptive text was categorized into Good. The result of analysis showed that average score of 24 students in translating descriptive text was 73.96. It is hoped that the finding of the present study will be useful for the teaching of English, especially in translating descriptive text.